RANCANGAN ALAT PEMBANGKIT LISTRIK TENAGA BATERAI - Hutapea, Bitson Nerpandi; Sirait, Ganda (LPPM Universitas Putera Batam, 2023)
Many factors could affect electricity distribution to seclusion places or the outer part of an island that needs electricity, for instance the power plant center is located very far away, low population, and difficult access to electricity. This is a design to establish a battery power generator that has the same concept with a common generator that could result in electricity power up to 36 kWh, this power can supply electricity to 30 houses with 1,2 kWh for each house. The goal of this research is to re-designing a generator by considering user needs. A survey had been made to acknowledge what customers might need from this product and axiomatic design is used to compile a parameter design using mapping process from customer attribute and functional requirement.